Families with mentally-ill member effects on other member of the family - Castillo, Ma. Vanna Rosa Lo
The study investigated the effects and coping strategies of family members with a mentally-ill member. Issues on psychological, physiological and social conditions as well as the spirituality of the respondents were considered in the study. It describes the behavioral changes affecting family members specifically on family relationship. Subjects were eight members of the families with a mentally-ill member. Mentally-ill members were afflicted with different types of mental disorders from Quezon City selected through convenience sampling. The respondents were between the ages 21-53 years. Responses were subjected to frequency and content analysis. Findings of the study showed that families with mentally-ill member prefer to engage assistance from health care providers for treatment and medication of the mentally-ill member. They opt to hide the problem in order to avoid different criticism from other people. Support groups from the government institutions was not an effective measure for families with mentally-ill member. Instead, building close relationship within the members emerged during the onset6 of mental illness to their family member.